Experimental characterization of steel tubular beam-columns resistance by means of the Overall Interaction Concept. (July 2018) - Hayeck, Marielle; Nseir, Joanna; Saloumi, Elsy; Boissonnade, Nicolas
Abstract: This paper presents a series of twelve buckling tests on rectangular and circular hollow section beam-column of nominal steel grade S355 . The columns were fabricated by either the hot-rolling or the cold-forming process, and were subjected to different load cases through the application of eccentric compression: mono-axial bending ( M y ) or bi-axial bending ( M y + M z ) combined with axial compression ( N ). Preliminary measurements of cross-section geometry, material properties, geometrical imperfections, residual stresses as well as stub column tests are also reported in this paper. The (imperfect) initial geometry was measured along the whole column by means of two different procedures; the first method relied on the use of a set of equally spaced Linear Variable Displacement Transducers (LVDTs) displaced on each specimen's plates. The second method consisted in scanning the specimen's plates by means of a laser Tracker AT401 . Residual stresses were also determined experimentally, and the sectioning technique was classically used to record the deformations of the released material; these results have been compared to measurements taken with electrical strain gauges. Finally, beam-column buckling strengths were plotted in an O.I.C.-type format, and complemented with an extensive experimental data collected from the literature that comprised various load cases, fabrication processes, yield strengths, cross-sections shapes, and elements' lengths. The O.I.C. approach was shown to adequately capture the behavior of hollow section beam-columns in a straightforward and simple manner, and its potential for efficiently and rationally predicting carrying capacities was evidenced.